2021
DOI: 10.3390/cells10092241
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cells and Exosomes: New Therapies for Intervertebral Disc Degeneration

Abstract: Intervertebral disc degeneration (IVDD) occurs as a result of an imbalance of the anabolic and catabolic processes in the intervertebral disc, leading to an alteration in the composition of the extracellular matrix (ECM), loss of nucleus pulposus (NP) cells, excessive oxidative stress and inflammation. Degeneration of the IVD occurs naturally with age, but mechanical trauma, lifestyle factors and certain genetic abnormalities can increase the likelihood of symptomatic disease progression. IVDD, often referred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 155 publications
0
51
0
1
Order By: Relevance
“…Studies have shown that MSC-Exos could prevent IDD by inhibiting apoptosis and promoting the proliferation of NPCs, inhibiting ECM degradation, alleviating inflammatory response and oxidative stress, promoting chondrogenic differentiation, and protecting endplate chondrocytes and annulus fibrosus. Therefore, MSC-Exos may be a promising option to delay or even reverse IDD (Hu et al, 2020;Krut et al, 2021). The related…”
Section: Relationship Between Msc-exos and Intervertebral Disc Degene...mentioning
confidence: 99%
“…Studies have shown that MSC-Exos could prevent IDD by inhibiting apoptosis and promoting the proliferation of NPCs, inhibiting ECM degradation, alleviating inflammatory response and oxidative stress, promoting chondrogenic differentiation, and protecting endplate chondrocytes and annulus fibrosus. Therefore, MSC-Exos may be a promising option to delay or even reverse IDD (Hu et al, 2020;Krut et al, 2021). The related…”
Section: Relationship Between Msc-exos and Intervertebral Disc Degene...mentioning
confidence: 99%
“…Therefore, interest in the use of exosomes for disc regeneration is increasing [160]. In the present scenario, for treating IVDD, only one clinical trial (phase 1) is being conducted in India; this trial involves using intradiscal injections of platelet-rich plasma that is enriched with exosomes in 30 participants [161]. Despite being a promising way of treating IVDD, various drawbacks and challenges still exist.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of proteoglycans is one of the primary manifestations of intervertebral disc degeneration. Therefore, restoration of proteoglycan content is required for degenerative disc repair [ 45 47 ]. This study showed that in the case of disc space recovery, the recovery of proteoglycan content was significant in LTT compared with HTT, with the LTT-4w groups scoring better than the LTT-2w groups.…”
Section: Discussionmentioning
confidence: 99%